Paradigma Baru Kelembagaan Koperasi Melalui Pentahelix Lewat Pemanfaatan Marketplace - Patricia Mutiara Karinta; Tarsisius Murwadji; Helza Nova Lita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Civil servants (ASN) entering retirement represent a strategic human resource asset for national development; however, their potential is often underutilized due to an institutional vacuum. This study identifies this fundamental problem as manifesting in two dimensions: the absence of a cohesive structure among the retired community and the lack of a structure that systematically connects them to the economic empowerment ecosystem. Consequently, the transition from active service to a productive retirement period presents a significant challenge. The purpose of this research is to design an effective institutional forum model to serve as a facilitative bridge. The analysis employs a framework integrating three pillars: Mochtar Kusumaatmadja's Development Law Theory as the philosophical foundation, Ansell and Gash's Collaborative Governance concept as the governance paradigm, and the Pentahelix model as the operational framework. This study proposes a multi-stakeholder collaborative forum designed to synergize the roles of government, industry, academia, communities, and the media. The primary recommendation is the establishment of a formal entity functioning as an incubator and accelerator. This entity is intended not only to address the economic needs of retirees but also to align with the country's constitutional mandate to achieve sustainable social welfare.